Maternal diet induces persistent DNA methylation changes in the muscle of beef calves - Rocío Amorín; Lihe Liu; Philipe Moriel; Nicolás DiLorenzo; Phillip A. Lancaster; Francisco Peñagaricano (Scientific Reports, 2023)
Abstract Maternal nutrition during pregnancy can induce epigenetic alterations in the fetal genome, such as changes in DNA methylation. It remains unclear whether these epigenetic alterations due to changes in maternal nutrition are transitory or persist over time. Here, we hypothesized that maternal methionine supplementation during preconception and early pregnancy could alter the fetal epigenome, and some of these alterations could persist throughout different developmental stages of the offspring. Beef cows were randomly assigned to either a control or a methionine-rich diet from − 30 to + 90 d, relative to the beginning of the breeding season. The methylome of loin muscle from the same bull calves (n = 10 per maternal diet) at 30 and 200 days of age were evaluated using whole-genome bisulfite sequencing. Notably, a total of 28,310 cytosines showed persistent methylation differences over time between maternal diets (q-value < 0.10, methylation change > 20%). These differentially methylated cytosines were in the transcription start sites, exons, or splice sites of 341 annotated genes. Over-representation analysis revealed that these differentially methylated genes are involved in muscle contraction, DNA and histone methylation, mitochondrial function, reactive oxygen species homeostasis, autophagy, and PI3K signaling pathway, among other functions. In addition, some of the persistently, differentially methylated cytosines were found in CpG islands upstream of genes implicated in mitochondrial activities and immune response. Overall, our study provides evidence that a maternal methionine-rich diet altered fetal epigenome, and some of these epigenetic changes persisted over time.